Secure Cloud Storage: A Protocol for Remote Data Integrity Checking - S, Naganandhini.; S.T, Shenbagavalli.; M., Shanmugapriya. (IJRDO -Journal of Computer Science Engineering, 2016)
The integrity of files stored on servers iscrucial for many applications running on the internet.Recently, many works provide data dynamics and/orpublic verifiability to this type of protocols. Remotedata possession checking protocols permit checkingthat, a remote server can access an uncorrupted file insuch a way that a verifier does not need to knowbeforehand the entire file. In addition, both datadynamics operations and public verifiability aresupported. Token pre-computation algorithm is used togenerate tokens. Challenge-Response protocol is usedfor communication between the challenger and theresponder. Through a formal analysis, the correctnessand security of the protocol is shown. After that,through theoretical analysis and experimental results,we demonstrate that the proposed protocol has a goodperformance.